2022
DOI: 10.3389/fonc.2022.891187
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa in Cancer Therapy: Current Knowledge, Challenges and Future Perspectives

Abstract: Drug resistance, undesirable toxicity and lack of selectivity are the major challenges of conventional cancer therapies, which cause poor clinical outcomes and high mortality in many cancer patients. Development of alternative cancer therapeutics are highly required for the patients who are resistant to the conventional cancer therapies, including radiotherapy and chemotherapy. The success of a new cancer therapy depends on its high specificity to cancer cells and low toxicity to normal cells. Utilization of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 131 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…The bacteria-based strategies have great promise in the treatment of tumors 68 . Various bacterial species including P. aeruginosa showed potent anti-tumor efficacy with or without modulating immune activity 69 . A recent report suggested that factors secreted from P. aeruginosa altered the proliferation of breast cancer cells and enhanced the activity of doxorubicin, suggesting that the signaling stimulated by factors secreted from P. aeruginosa is dependent on the abundance of P. aeruginosa 70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteria-based strategies have great promise in the treatment of tumors 68 . Various bacterial species including P. aeruginosa showed potent anti-tumor efficacy with or without modulating immune activity 69 . A recent report suggested that factors secreted from P. aeruginosa altered the proliferation of breast cancer cells and enhanced the activity of doxorubicin, suggesting that the signaling stimulated by factors secreted from P. aeruginosa is dependent on the abundance of P. aeruginosa 70 .…”
Section: Discussionmentioning
confidence: 99%
“…1 , 3 ). Furthermore, several proteins from P. aeruginosa such as azurin, exotoxin A (ExoA), exoenzyme T (ExoT), Pacaspase recruitment domain (Pa-CARD) have been found to exert potent cytotoxicity against cancer 69 . Moreover, azurin can enhance the efficacy of standard chemotherapeutic agents such as 5-fluorouracil (5-FU) 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroglioma is a life-threatening malignant tumor, and traditional radiotherapy is not very effective. More and more studies have shown that microorganisms and their derivatives can be used as cancer therapies, which mainly include three kinds: 1. microbial derivatives used in glioma therapy, bacteria can produce active substances such as bacteriocins and antimicrobial peptides, which are used in the treatment of gliomas through different mechanisms [113][114][115]; 2. phages can target gliomas for drug delivery, and phages have a strong affinity for the VAV3 protein GICP (glioma-initiating cell peptide), which has a strong affinity for VAV3 protein, and phages can be used to precisely deliver drugs to gliomas [116]; 3. Microbial targeting of gliomas, where many bacteria can cross the blood-brain barrier to enter the center through a unique mechanism, which lays the groundwork for bacterial entry into targeted gliomas, and where viruses have their own mechanisms or use immune cells as carriers, which, when administered systemically, can cross the blood-brain barrier and enter gliomas.…”
Section: Gut Flora In Head and Neck Tumorsmentioning
confidence: 99%
“…PE, the most aggressive virulence factor produced by Pseudomonas aeruginosa, can be employed to destroy tumor cells by inhibiting protein synthesis via ADP-ribosylation of eukaryotic elongation factor 2. PE can be combined with antibodies or receptor ligands for precise tumor targeting to generate chimeric proteins, and this toxin-linked targeting element forms an immunotoxin that can be exploited for cancer therapy [ 33 ]. The targeting element is responsible for attaching tumor surface molecules, while the toxin kills cancer cells.…”
Section: Exogenous Microorganisms and Their Derivatives For Glioma Tr...mentioning
confidence: 99%